Transforming cultural conflict in the foreign language classroom: the case of Arabic at Defense Language Institute. (2nd January 2018) - Barrett, Tyler; Trosky, Abram; Tawadrous, Adel
Abstract: This paper considers the impact of global and national political polarisation on perspectives of instructors and learners in Arabic classrooms at Defense Language Institute Foreign Language Center (DLIFLC) in the United States with particular interest in understanding cultural conflicts that occur between instructors and learners. Instructors and learners at DLIFLC responded to a survey, the qualitative data from which are analysed using discourse analysis, research in intercultural communication, and theories of pedagogy. The analysis indicates that while cultural conflict is part of the language-learning experience, there are communicative strategies to turn moments of discord into assets which often involve the ancillary role of non-native speaking instructors who assist in preventing and mediating conflict between native-speaking instructors and students. The paper begins with a brief literature review that informs our theoretical framework, and a description of the study, followed by an analysis of the data it generated and discussion of their implications for DLIFLC and similarly-situated classrooms.